Graphene: A Supramolecular Strategy to Leverage the Liquid‐Phase Exfoliation of Graphene in the Presence of Surfactants: Unraveling the Role of the Length of Fatty Acids (Small 14/2015). Issue 14 (April 2015) - Haar, Sébastien; Ciesielski, Artur; Clough, Joseph; Yang, Huafeng; Mazzaro, Raffaello; Richard, Fanny; Conti, Simone; Merstorf, Nicolas; Cecchini, Marco; Morandi, Vittorio; Casiraghi, Cinzia; Samorì, Paolo
<x xml:space="preserve">Abstract</x> A supramolecular approach for producing homogeneous dispersions of graphene nanosheets in various solvents is described by A. Ciesielski, P. Samorì, and co‐workers on page 1691. Comparative studies of the liquid‐phase exfoliation of graphene in the presence of linear alkanes of different lengths terminated by a carboxylic‐acid head group reveal that they molecules act as graphene dispersion‐stabilizing agents during exfoliation. The efficiency of exfoliation in terms of the concentration of exfoliated graphene is found to be proportional to the length of the fatty acid. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>